Development of a material balance equation for coalbed methane reservoirs accounting for the presence of water in the coal matrix and coal shrinkage and swelling. (March 2015) - Thararoop, Prob; Karpyn, Zuleima T.; Ertekin, Turgay
Abstract: The effects of water presence in the coal matrix and coal shrinkage and swelling phenomena are often ignored in the production performance predictions of coalbed methane reservoirs. This paper presents the development of a new material balance formulation for coalbed methane reservoirs that accounts for water presence in the coal matrix and coal shrinkage and swelling phenomena. The development entails the governing gas and water flow equations in dual-porosity, dual-permeability coalbed methane reservoirs. Various comparative studies are conducted to investigate the capabilities of the proposed and existing material balance equations using the production data generated from a robust two-phase, dual-porosity, dual-permeability coalbed methane simulator developed at Penn State. The results show that exclusion of the two aforementioned phenomena in coalbed methane material balance formalisms reduces the estimated reservoir production capacity resulting in under-predictions of reservoir size. In addition, iterative methods for predicting production performance and average reservoir pressure using the proposed material balance formulation are developed and successfully tested against the simulation model.